Perbedaan Kecukupan Asi Antara Akseptor KB Suntik Kombinasi Dengan KB Suntik Progestin Pada Ibu Menyusui 0-6 Bulan Di Wilayah Kerja Puskesmas Sambirejo Sragen - Chelia Ercy Adnara; Dwi Retna Prihati; Henik Istikhomah (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: Nursing mothers who do not want to get pregnant anymore need safe contraception, do not interfere with the breastfeeding process and do not affect breast milk production. Injection contraception is divided into two, namely combined injection family planning and progestin injection family planning. Combined injection family planning contains the hormone estrogen which can reduce the amount of breast milk production, while injectable progestin family planning contains the hormone prolactin which can stimulate the production of breast milk glands. One of the factors that influence the adequacy of breast milk is the use of contraception. Method: Type of observational research with cross sectional design. The sample in this study were all breastfeeding mothers who used injection contraception in the work area of ​​Sambirejo Health Center Sragen in September to November 2018 as many as 62 people. Total sampling technique, chi square analysis. Results: Characteristics of acceptor age, namely 20-35 years as many as 52 people (83.9%) education namely high school as many as 30 people (48.4%), occupations namely housewives as many as 46 people (74.2%) and parity is primipara 33 people (53.2%). The adequacy of breastfeeding in breastfeeding mothers who use combined injection contraception is mostly 16 people (25.8%) and not enough as many as 12 people (19.4%). The adequacy of breastfeeding in breastfeeding mothers who use the progestin injection contarction is mostly 32 people (51.6%) and not enough as many as 2 people (3.2%). The chi square test results p = 0.001 (p <0.05). Conclusion: There is a difference in the adequacy of breastfeeding between family planning injection acceptors combined with Progestin injections in breastfeeding mothers 0-6 months in the working area of ​​Sambirejo Sragen health center.